The la-form: Russian verbs in Nanai speech - Oskolskaya, Sofia; Stoynova, Natasha (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2013)
Nanai speakers who are fluent both in Nanai and Russian use verb forms with a Russian root and the suffix -la (called further “la-forms”) in their speech. The status of -la is under question: on the one hand, it resembles the Russian past tense form (-l), on the other hand, it can be interpreted as the Nanai derivational suffix -la/-lə, which is used in Standard Nanai for the verbalization of nouns. We argue that in modern Nanai this case turns out to be a complicated one, and that la-forms are maintained due to their links with both of these sources.